2021
DOI: 10.1007/s11469-020-00456-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact of COVID-19 Among People from the Banking Sector in Bangladesh: a Cross-Sectional Study

Abstract: Despite the pandemic, the Government of Bangladesh decided to keep the banks open to a limited extent to keep the country's economy afloat. The aim of this study is to assess the psychological impact of COVID-19 among the bankers who are usually more exposed to random people that put them at great risk to be affected. A total of 248 bankers willingly answered our questionnaire consisting of DASS-21 and relevant questions. Cronbach's reliability coefficient for the DASS-21 scale ranges from 0.84 to 0.90 which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 13 publications
4
49
0
3
Order By: Relevance
“…Mamun et al (30) reported that 15.6% of the participants were depressed who were involved with smoking, whereas this rate was 3.3% for alcohol users. Besides, another study reported that those who were smoking more frequently signi cantly experience a high score for stress and depression (39).…”
Section: Behavior and Health-related Risk Factors A Smoking And Alcohol Usementioning
confidence: 99%
See 4 more Smart Citations
“…Mamun et al (30) reported that 15.6% of the participants were depressed who were involved with smoking, whereas this rate was 3.3% for alcohol users. Besides, another study reported that those who were smoking more frequently signi cantly experience a high score for stress and depression (39).…”
Section: Behavior and Health-related Risk Factors A Smoking And Alcohol Usementioning
confidence: 99%
“…Therefore, fear of being infected also increases their risk of being affected mentally. Nevertheless, only a study was directed among bankers regarding the level of anxiety, depression and stress, which includes 10.6%, 12.1% and 11.1%, respectively; the lowest prevalence rates as identi ed across all of the cohorts included in this review (39).…”
Section: Prevalence Of Mental Disorders: Bankersmentioning
confidence: 99%
See 3 more Smart Citations